Pour une exploitation linguistique des anciens manuscrits berbères et arabo-berbères en graphie arabe. Essai de valorisation numérique - Meziani, Noumidya (Université El-Hadj Lakhdar, 2025)
Keywords: Linguistique

Grammaire fonctionnelle de l'arabe du Coran : inventaire des classes et syntaxe - Nedjar, Bahmani (Université Paris 5, 1986)
Keywords: Linguistique

Description du berbère de Guellala : parler d'un village de l'île de Djerba (Tunisie) - Belhouane, Jihane (Sorbonne université, 2018)
Keywords: Linguistique

Морфология и морфонология языка джерби. во внутригенетической типологической перспективе - Filippov, Nikolay (Institut d'État de Moscou Lomonosov, 2019)
Don de l'auteur
Keywords: Linguistique

Language Maintenance and Language Shift among the Berbers Imazighen of Djerba Southern Tunisia - Bouhdima, Mohamed Elhedi (Institut Supérieur des Langues de Tunis)
The purpose of this study is to investigate the situation of Amazigh Berber language in Djerba an island located in the south-east of Tunisia The study will focus on four Djerbian adjective from Djerba villages mentioned in previous publications Maamouri 1973 Pencheon 1983 as being Berberspeech zones namely Guellala Ajim El-Mai and Sedouikech Studying the plight of Amazigh language henceforth AL in these areas will include an investigation into the factors of language maintenance LM and those of language shift LS Put differently the study will be concerned not only with the factors underpinning AL maintenance but also with those contributing to the shift from AL to Tunisian Arabic henceforth TA the dominant language of Tunisia
Keywords: Linguistique

Berber a dying language in Djerba - Ferjani, Olfa (Faculté des Sciences Humaines et Sociales, 2002)
Keywords: Linguistique

An Outline of the Shilha (Berber) Vernacular of Douiret (Souther Tunisia) - Gabsi, Zouhir (University of Western Sidney, 2003)
Keywords: Linguistique

Etude de la commune de Guellala à Djerba (Tunisie) : une des dernières localités berbères - Hadjam, Aoussia (Université Paris 8, 2013)
Keywords: Linguistique

Le parler arabe des Juifs De Djerba. Étude linguistique - Ben Mbarek, Hala (Inalco, 2001)
Keywords: Linguistique

Etude sociolinguistique de la minorité Amazighophone de Djerba - Ben Omrane, Walid (Faculté des Sciences Humaines et Sociales, 2004)
Keywords: Linguistique

Dialecte berbère de Guellala (Jerba-Tunisie,) Lexique thématique tamazight – français - Ben Daamar, Fadia (Université de Kairouan, 2011)
Keywords: Linguistique